Research of Correlation of Theoretical Knowledge and Psychomotor Skills of Pupils in Technical Education - Žácok, Lubomír; Bernát, Milan; Bernátová, Renáta; Pavlovkin, Ján (European journal of contemporary education, 2020)
The authors of the scientific study examine the impact of the relationship of theoretical knowledge on practical skills in technical subjects at the lower secondary level of education in the Slovak Republic. After determining the research problem and hypotheses, they bring the processed results in the form of tables and figures. Quantitative results within the pedagogical experiment are supplemented by qualitative analysis. In a scientific study, we characterize a research sample and research methods. We focus on a detailed description of problem tasks that pupils have solved in pedagogical research. Pedagogical research was carried out in four regions in the Slovak Republic. At the end of the scientific study, the authors compare the results ascertained from previously published information in the field of science. We are based on modern approaches in pedagogy, which integrate the issue of assessing pupils psychomotor skills into the field of general education. The current objectives and tasks in subjects developing cognitive knowledge and psychomotor skills of pupils and specifically on the subject of technology, represent a body of knowledge and skill to be learned. In the information society, knowledge is growing in a geometric way, especially in the field of technical sciences. The knowledge that the pupil acquires at school will no longer be sufficient after solving the internship in solving the technical problems he will encounter. Scientific studies address this issue. We examine the influence of theory on the acquisition of practical skills. Both aspects are important in the development of the pupils' personality not only in the technical but also in the modern information society.